Membangun Nilai Kasih Persahabatan dalam Pemberian Kerbau atau Babi dalam Upacara Rambu Solo’ - Yayu Astuti Lampi (Jurnal Teologi Kontekstual Indonesia, 2023)
Toraja One of the cultures that is popular for its exquisite culture both inside and outside of Indonesia. The Rambu Solo’ ceremony, a death event that is widely celebrated in Toraja, is one of the most well-known. There is a tradition in the ritual "Rambu Solo’ " of bringing buffalo or pig for family members or close friends who are in mourning. Giving in this way today is changing and leading to a new view of debts and receivables that must be repaid. The purpose of this essay is to explore the real significance of providing buffalo or pigs, also known as tangkean Suru’.This article employs a descriptive qualitative research methodology. According to the study's findings, giving buffalo or pigs as part of the Rambu Solo’ ceremony is a type of sipopa’di, Siporannu and siangkaran.